Comparison of Lavandula officinalis tincture and imipramine in the treatment of mild to moderate depression: a double-blind, randomized pilot study - M Khani; H Vazirian; AH Jamshidi; A Kamalipour; L Kashani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2002)
Depression is a major health problem and is not only underrecognized and undertreated but is associated with significant morbidity and mortality. Lavandula officinalis is used to treat depression. Our objective was to compare the efficacy of tincture of Lavandula officinalis with imipramine in the treatment of mild to moderate depression and to evaluate the possible adjuvant effect of this tincture in a 4 week double-blind, randomized pilot study. 45 adult outpatients who met the Diagnostic and Statistical Manual of Mental Disorders, 4th edition for major depression based on the structured clinical interview for DSM-IV participated in the trial. Patients has a baseline Hamilton Rating Scale for Depression score at least 18. In this double-blind, single-center trial, patients were randomly assigned to receive Lavandula tincture 60 drops/day plus placebo tablet (Group 1) tablet imipramine 100 mg/day plus placebo drop (Group 2) and tablet imipramine 100 mg/day plus Lavandula tincture 60 drops/day, for a 4-week study. In this small preliminary double-blind and randomized comparison of Lavandula tincture and imipramine in the treatment of mild to moderate depression Lavandula was found to be less effective than imipramine. Nevertheless, combination of imipramine and lavandula tincture was more effective than imipramine alone. As this study indicates, one of the advantages of this combination is a rapid onset of activity. In addition, in the imipramine group anticholinergic effects such as dry mouth and urinary retention were observed more often that was predicatable whereas headache was observed more in the lavandule tincture group. The main overall finding from this study is that lavandula tincture may be of therapeutic benetit in the management if mild to moderate depression. A large- sxale trial is justified.